1989
DOI: 10.1007/bf00195793
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal velocity and turbulence measurements downstream of a model multilobed turbofan mixer

Abstract: An isothermal experimental investigation of the three dimensional flow field downstream of a model multilobed turbofan forced mixer is presented. LDA measurements of the three mean velocities and corresponding turbulence intensities were obtained in the downstream duct where the turbine (primary) and fan (secondary) streams emerging from the lobes mix together. The flow development in the near field was quantified by measuring the crossplane velocities. These were found to consist of large radial flows, of ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For the basic single-lobe forced mixer, from equations ( 10) to (13), the relationships between the Reynolds number (defined as equation ( 3)) and the Strouhal number are as follows, for example…”
Section: Strouhal Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…For the basic single-lobe forced mixer, from equations ( 10) to (13), the relationships between the Reynolds number (defined as equation ( 3)) and the Strouhal number are as follows, for example…”
Section: Strouhal Numbermentioning
confidence: 99%
“…Povinelli et al [8] and Paterson [9,10] subsequently found that there were large-scale secondary motions in the wake of the lobed forced mixer while conducting the NASA energy efficient engine (E 3 ) investigation programmes. Researchers such as Presz et al [5], Barber et al [11], Skebe et al [12], Koutmos and McGuirk [13], Eckerle et al [14], Abolfadl and Sehra [15], Presz et al [16], Tew et al [17], Yu and Yip [6], Yu and Xu [18] studied the fluid dynamic characteristics of the lobed forced mixer either experimentally or numerically. The gross features of the flow field were examined in their investigations, and mostly focused on the formation and development of the streamwise vortices.…”
Section: Introductionmentioning
confidence: 99%
“…The relative streamwise kinetic energy is given, for the summation of up to the <7th POD mode, as (5) As q goes to N, where TV is the total number of eigenvalues and eigenfunctions, the value of E q will approach 1. shows values ofE 9 plotted vs q for both downstream locations at y/h =0.75 (similar behavior was observed for the other y/h positions). From this curve it can be inferred that the larger scales, represented by the first few modes, contain the majority of the energy at z/h = 2.6.…”
Section: Convergence Of the Podmentioning
confidence: 99%
“…Thus, they represented a positive contribution in the first two terms for the u' 2 components (Equation (3)). However, for the third terms in Equations (4) and (5), they suggested a negative contribution for the v' 2 and w' 2 components respectively (the gradients of dVlax and dWIdx were negative).…”
Section: Development Of the Reynolds Stressesmentioning
confidence: 99%